Arrival patterns of Greylag Geese Answer answer in the Guadalquivir Marismas - Persson, Hakon (Wildfowl, 1993)
Studies of neck-banded Greylag Geese in southwestern Spain reveal that there are two subpopulations, one Baltic and one Norwegian, which possess completely different timing with respect to their autumn migration. By 22 November, more than 80% of all neck-banded Baltic Greylags, but only one quarter of the Norwegian ones, were spotted. All Baltic geese arrive before New Year, while the arrival of Norwegian Greylags continues until the end of February. Differences were also found between marking areas, age groups, and breeding lakes.